Pertumbuhan Bibit Tembakau (Nicotiana tabacum L.) Beberapa Varietas Lokal dan Unggul dengan Media Polibag - Qadri, Sri Nur; Yamin, Mayasari; Darwis, Dzulkifli (Journal Galung Tropika, 2023)
Tobacco (Nicotiana tabacum L.) is a commercial crop that plays a role in the economy. Tobacco productivity can be increased by optimizing existing land. One component of tobacco cultivation that supports tobacco growth is the availability of quality planting material. The aims of this research are 1) To determine the growth response of tobacco plant seeds in several local and superior varieties and 2) To determine the growth rate of tobacco plant seeds in several local and superior varieties. It was carried out at the Experimental Garden of the Faculty of Agriculture, Animal Husbandry, and Fisheries from June to September 2023. The design used was a non-factorial randomized block design repeated 3 times, each treatment consisting of 4 samples. The treatments tested were 4 varieties of tobacco, namely Ico Lalo (V1), Ico Tempo (V2), Kemloko (V3), and Prancak-95 (V4), so there were 48 experimental units. The results of the research showed that the Kemloko 1 variety had the best seed growth for observed characters, namely plant height, 10,425 cm; stem height, 2,943 cm; leaf length, 6,475 cm; and leaf width, 4,483 cm. The description of the kemloko 1 variety shows that the level of location specificity is better than that of superior and local varieties according to the observed characteristics, namely plant height, stem height, leaf length, and leaf width.